Indonesian Ulema Council Fatwa on Interfaith Greetings: Its Impact on Islamic Tolerance and Family Law - Suganda, Ahmad; Rahman, Encep Taufik; Ahyani, Hisam; Dunur'aeni, M. A. E.; Rozikin, Opik; Lousada, Sérgio António Neves; Ahmad, Md Yazid (FIKRAH, 2024)
The MUI fatwa related to interreligious greetings has created polemics in Indonesian society, particularly in the context of Islamic moderation. This fatwa prohibits interreligious greetings which are considered to damage the purity of Islamic teachings that affect social relations, especially in families that have different beliefs. This article aims to analyse the impact of the MUI fatwa on the dynamics of family law in Indonesia, especially on families who have different beliefs and their relevance to the principles of Islamic moderation in the context of family law. This article uses a qualitative approach with an analysis of the content of the MUI fatwa related to greetings in family law, and interviews with family law experts and religious leaders who understand the implications of the fatwa on family relations in interfaith Indonesian society. This article shows that the MUI Fatwa causes tension in families of different beliefs regarding interfaith greetings. This fatwa also shows the tension between maintaining religious identity and maintaining family harmony. In the context of family law, this fatwa affects basic principles such as respect for religious differences and the values of inclusivity in families of different religions. This article offers a new perspective that connects the MUI fatwa related to interfaith greetings with family law in Indonesia.